2020
DOI: 10.1038/s41598-020-77074-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and static properties of stadium-shaped antidot arrays

Abstract: In this work we performed a detailed numerical analysis on the static and dynamic properties of magnetic antidot arrays as a function of their geometry. In particular, we explored how by varying the shape of these antidot arrays from circular holes to stadium-shaped holes, we can effectively control the magnetic properties of the array. Using micromagnetic simulations we evidenced that coercivity is very sensitive to the shape of antidots, while the remanence is more robust to these changes. Furthermore, we st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…In this case, the magnetic field activates resonant modes that depend on the magnetic configuration of the nanostructure. We highlight that the pulse amplitude is small enough to ensure that the magnetic response of the system is in the linear regime [66,67]. The system's magnetization dynamics was determined from the model presented in section 2 and the results are presented in figures 3(b) and (c), which illustrate the frequency of the resonance modes as a function of H. To simplify our analysis, we focus only on those modes that are higher than 4% of the intensity of the main mode for H = 0.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the magnetic field activates resonant modes that depend on the magnetic configuration of the nanostructure. We highlight that the pulse amplitude is small enough to ensure that the magnetic response of the system is in the linear regime [66,67]. The system's magnetization dynamics was determined from the model presented in section 2 and the results are presented in figures 3(b) and (c), which illustrate the frequency of the resonance modes as a function of H. To simplify our analysis, we focus only on those modes that are higher than 4% of the intensity of the main mode for H = 0.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, significant advances in the study of single nanomagnet dynamics were reported when Rana et al investigated the time-resolved precessional magnetization dynamics of an isolated 50 nm-wide square permalloy dot, revealing a dominant mode known as the edge mode (EM), in addition to the center mode (CM). It has been widely observed that the EM mode generally outweighs the CM, primarily because the EM is highly sensitive to imperfections, as well as variations in dot shape and size. Thus, conducting simulations allows us to examine the quasi-static and dynamic aspects of magnetization, facilitating a comprehensive understanding of magnetic phenomena that are crucial for electrochemical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, there has been a noticeable upsurge in the publication of studies employing micromagnetic simulation software, such as OOMMF 16 or MuMax3, 17 either to bolster experimental findings or as a fundamental theoretical framework. Notably, researchers have extensively investigated the ferromagnetic resonance properties of a broad spectrum of magnetic nanosystems, including tubes, 18 wires, 19 dots, 20 rings, 21 and thin films, 22 among others. These investigations have consistently revealed that nanomaterial shapes and magnetic parameters can lead to distinct dynamic susceptibility behaviors.…”
Section: Introductionmentioning
confidence: 99%